PROSES KREATIF SISWA HOMESCHOOLING DALAM PENCIPTAAN MUSIK MELALUI PEMBELAJARAN GITAR (STUDI KASUS : KELAS GITAR SANGGAR REGENERASI) - Sasmita, Pelangi Dienna Deyane (Institut Seni Indonesia (ISI) Surakarta, 2021)
Guitar learning are held in formal institutions such as schools, generally only give basic theoretically teaching about music or just how to play a musical instrument well. The same thing is often found in many music courses. However, in the case of the Sanggar Regeneration guitar class, beside doing guitar lesson, students are often able to produce musical works. Guitar learning in the Sanggar Regeneration guitar class are conducted by mentors to homeschooling students of PKBM Semesta Ilmu. This research shows that the guitar learning process at Sanggar Regeneration also includes the transmission process and creativity in it. In this case, knowledge between mentors and homeschooling students is carried out and becomes continuous learning. The highlight of this guitar learning is a change in behavior in the form of students' ability to play the guitar. Through this guitar learning process students are also active and critical, so that students' creativity can emerge based on their practice and experience. This has an impact on students and is developed into innovative products, one of which is the music of the homeschooling student.